Social Media Promotion Design On Master Bakery Instagram Platform - Dessy Aliandrina; Yeni Wulandari (Universitas Internasional Batam, 2023)
The growth of internet users can assist a business in conducting online marketing which is useful for business owners to interact and quickly provide the latest promotional information to consumers. One form of online marketing through social media is Instagram. Instagram is used for business owners to introduce their products. One business that uses Instagram as online marketing is a bakery. Instagram can be a place for a baker to show his product and increase awareness among his consumers and can be used for business development, thereby facilitating the development of MSMEs in this digitalization era.